Pengaruh Kepemilikan Institusional terhadap Nilai Perusahaan dengan Kebijakan Hutang dan Kinerja Keuangan sebagai Variabel Mediasi : (Studi Empiris pada Perusahaan Manfaktur yang Terdaftar di Bursa Efek Indonesia) - Yuni Kurniawati; Heru Sulistiyo; Sodikin Manaf (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to determine the effect of Institutional Ownership on Company Value with Debt Policy and Financial Performance as mediating variables. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The research sample used purposive sampling and produced 32 company samples, with 5 years of observation or 160 samples, after processing 13 were outliers, so that the final sample was 147. The data analysis method used path analysis and data processing using SPSS. This study uses quantitative analysis, including classical assumption tests (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), path analysis test, model feasibility test (t-test, F-test, coefficient of determination). The results of the t-test show that Institutional Ownership partially has a significant positive effect on Debt Policy. Institutional Ownership has a negative but insignificant effect on Financial Performance. Institutional Ownership has a significant positive effect on Company Value. Debt Policy has a significant positive effect on Firm Value. Financial Performance has a significant positive effect on Firm Value. The results of the analysis using the Sobel test indicate that Debt Policy and Financial Performance do not mediate the effect of Institutional Ownership on Firm Value.